Bacillus spp. supplementation promotes feed efficiency in mid- to late-lactation dairy cows and affects rumen fermentation traits of rumen-fistulated females offered a corn silage–based total mixed ration diet - Bruno A.V. Arthur; Luiz Gustavo Nussio; Oscar C.M. Queiroz; Greicieli de Morais; Rafael H.P. Reis; Giuseppe Copani; Jens N. Joergensen; Bruno I. Cappellozza (JDS Communications)
Two experiments evaluated the effects of supplementing a Bacillus-based direct-fed microbial (DFM) on productive performance of mid- to late-lactating dairy cows (experiment [Exp.] 1), and on rumen fermentation traits of rumen-fistulated Holstein cows (Exp. 2). In Exp. 1, 60 mid-lactating (126 ± 11.5 DIM), primiparous (n = 14), and multiparous (n = 46) Holstein cows were blocked, within parity, by milk yield into (1) TMR (CON; n = 30) and (2) CON with Bacillus licheniformis 809 and Bacillus subtilis 810 (n = 30; BAC). Diets were offered for 12 wk, following a 3-wk covariate period. All cows received a corn silage–based TMR throughout the study. Dry matter intake and milk yield were evaluated daily, whereas milk, blood, and fecal samples were collected on wk 4, 8 and 12 for milk composition, metabolite analysis (urea and glucose), and nutrient digestibility, respectively. In Exp. 2, 16 rumen-fistulated nonlactating multiparous Holstein cows were ranked by initial BW and assigned to the treatments described in Exp. 1. The experimental period lasted 25 d and samples were taken on d 22 to 25 for in situ DM degradability, rumen ammonia, and pH. All data were analyzed with the MIXED procedure of SAS using cow as the experimental unit. In Exp. 1, DMI was reduced in BAC-fed cows, but no differences were observed on milk yield. Cows offered BAC had a grater feed efficiency versus CON (+100 g/kg feed). Bacillus spp. supplementation increased milk fat content, reduced MUN, and tended to reduce milk protein content. Mean BUN was reduced and plasma glucose was greater in cows fed BAC. No treatment effects were observed for DM or starch digestibility, but NDF digestibility was greater for BAC-fed cows. In Exp. 2, a treatment × hour interaction was observed on DM degradability, being greater at 12 h postfeeding in BAC cows versus CON. Rumen pH tended to be greater for BAC at 12, 24, and 72 h, whereas mean rumen pH and DM degradability were greater in BAC. In summary, feeding a Bacillus-based DFM to mid- to late-lactating dairy cows improved feed efficiency and increased mean glucose, while also stimulating DM and NDF digestibility.